Scientific Basis Of Development Of Eydecological Relations In Primary Classes (Eurasian Scientific Herald, 2022)
In this article,the idea of the formation of eidecological relations in primary schoolchildren, that this relationship is a feature of nature, the impact of environmental education of a person is expressed. Also, the fact that the child is one of the natural organisms and an ecological factor, the pedagogical, physical aspects of the child's efforts to make changes in harmony with the purposeful actions set in nature are highlighted.